2001
DOI: 10.1111/1467-9280.00328
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Attitude Measures: Consistency, Stability, and Convergent Validity

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
648
2
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 799 publications
(728 citation statements)
references
References 27 publications
68
648
2
10
Order By: Relevance
“…However, this interpretation requires caution. Given that correlations between implicit measures and effect sizes can be attenuated by measurement error (e.g., method-related variance, internal consistency; Bar-Anan & Nosek, 2014;Baugh, 2002;Cunningham, Preacher, & Banaji, 2001) and that our studies may have been underpowered, future research is needed to provide additional evidence for the possibility that, even for young children, these measures tap into different constructs (e.g., BarAnan & Nosek, 2014;Gawronski & De Houwer, 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation requires caution. Given that correlations between implicit measures and effect sizes can be attenuated by measurement error (e.g., method-related variance, internal consistency; Bar-Anan & Nosek, 2014;Baugh, 2002;Cunningham, Preacher, & Banaji, 2001) and that our studies may have been underpowered, future research is needed to provide additional evidence for the possibility that, even for young children, these measures tap into different constructs (e.g., BarAnan & Nosek, 2014;Gawronski & De Houwer, 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a psychometric caveat here that precludes drawing firm theoretical conclusions-the reliability of measurement. Specifically, affective priming measures have been repeatedly criticized for their low reliability (e.g., Cunningham, Preacher, & Banaji, 2001), and these differences may account for large portions of this moderator effect. Note, however, that an interpretation in terms of reliability faces some difficulties in explaining the gap between the magnitude of EC effects for self-report as compared with IAT measures because internal consistencies of the IAT typically are around .80 (e.g., Hofmann, Gawronski, Gschwendner, Le, & Schmitt, 2005) and thus similar to those commonly obtained for self-reports.…”
Section: What Are the Processes Underlying Evaluative Conditioning?mentioning
confidence: 99%
“…Cunningham et al (2001), for example, found that the correlation between the IAT (Greenwald et al, 1998) and affective priming (Fazio et al, 1995) is only moderate, even when measurement error is controlled. This finding may indicate that the nature of the associations assessed with these tasks have only partial overlap (e.g., Olson & Fazio, 2003).…”
Section: Implications and Future Directionsmentioning
confidence: 99%